The ‘I was here’ syndrome in tourism: The case of Poland - Chylińska, Dagmara; Kosmala, Gerard (Quaestiones Geographicae, 2023)
Tourism appropriates tourist attractions and takes possession of them, marking them both physically and symbolically. Tourists visiting attractions tend to create distinctive marks, usually characterised by some significance in terms of self-identification, on the places and monuments visited by them, and this could be regarded as a symptom of a specific ‘I was here’ syndrome; in the present study, the authors examine the prevailing practices of marking attractions in tourist spaces, as also the marks themselves. We endeavour to identify the nature of the phenomenon and the consequences for both the attractions and the subjects managing them. The survey carried out involved sev- eral chosen sites in Poland, all of which are characterised by a recognised historic status in the realm of public space as well as a clearly identified sociocultural or legal value, which by definition imposes the requirement for adhering to a certain behavioural code when within their precincts and towards them, and excludes other kinds of behaviour. These attractions are all subject to different forms of institutionalised control, which, however, fails when it comes to safeguarding them from the practices of marking undertaken typically by tourists; these occurrences have become a routine phenomenon, which is unsurprising given the fact that the rituals of the contemporary mass and mediatised tourism have made this kind of tourist behaviour common, albeit on a lower scale than previously expected.